Islamic Perspectives on Multicultural Education Values in The Sumberdem Clean Village Tradition - Ummi Ulfatus Syahriyah; Ilma Fahmi Aziza; Islahuddin Islahuddin (El Harakah)
Multiculturalism emerges as a force promoting diversity within the global system, driving the creation of true social justice. However, this concept is not universally accepted; some people reject it, viewing it as obscuring the essence of religion. This research aims to describe the values of multicultural education embedded in the Clean Village tradition in Sumberdem Village, examining them from the perspective of Islamic teachings. The research employs a qualitative method with a phenomenological approach. Data collection involved in-depth interviews, observations, and documentation, followed by interpretive phenomenological analysis. The findings reveal that the multicultural values expressed in the Clean Village tradition include social care, consensus, mutual cooperation, respect for diversity, and fairness. These values align harmoniously with Islamic teachings, offering solutions to humanitarian challenges by weaving diversity into a cohesive social fabric. This process shapes a well-rounded individual who balances their roles as abdullah (God’s servant) and khalifatullah (God’s steward). This tradition can serve as a model for integrating multicultural values into community practices, especially in diverse cultural and religious settings, fostering inclusive environments that promote mutual respect and collective well-being, in alignment with both secular and religious frameworks for social harmony.